Oxidative purification of carbon nanotubes and its impact on catalytic performance in oxidative dehydrogenation reactions - Rinaldi, A.; Zhang, J.; Frank, B.; Su, D.S.; Hamid, Sharifah Bee Abd; Schloegl, R. (Wiley, 2010)
Oxidative purification with mild diluted HNO(3) followed by NaOH washing lowers the amount of amorphous carbon attached to multiwalled carbon nanotubes (CNTs). The graphitic structure improves remarkably by further annealing in argon at elevated temperatures, that is, 1173, 1573, and 1973 K. The influence of the purification treatment on the catalytic activity of the CNTs is investigated for the oxidative dehydrogenation (ODH) of ethylbenzene and propane as probe reactions. All samples tend to approach an appropriately ordered structure and Raman analysis of the used samples displays a D/G band ratio of 0 95-1 42. Oxygen functionalities are partly removed by the annealing treatment and can be rebuilt to some extent by oxygen molecules in the ODH reactant flow. The presence of amorphous carbon is detrimental to the catalytic performance as it allows for unwanted functional groups occurring in parallel with the formation of the selective (di)ketonic active sites